Elderly Women - Aghacy, Samira (1999)
Given that the year 1999 has been designated by the United Nations as the International Year for Older Persons with the theme Towards a Society for all Ages,' the File for this issue of Al-Raida is devoted to elderly women. Since the problem of aging in Lebanon is not as drastic as it is in Western and developed countries, we are fortunate to have the time to prepare ourselves, plan ahead and determine whether the measures taken by these countries to alleviate the problems of their aged citizens are also relevant to our culture and society.